Educational models and technologies in the era of digital transformation - T. L. Salova (Вестник Майкопского государственного технологического университета, 2024)
At present digital transformation of the society faces the problem of a shortage of a highly qualified personnel - specialists in the field of the latest information technologies, intellectual scientists with a high-quality fundamental education. The solution to this problem lies in the introduction of new educational models and technologies.   The purpose of the research is to study the strategy for the formation of a new conceptual scheme of modern education.   It has been emphasized that two leading educational models are currently being successfully implemented and complement each other: the classical model of «completed» education with the basic principle of «education once and for life», covering the need of the society for the generation and dissemination of knowledge, as well as the storage of cultural ideals, and the second model, called the «lifelong education model», which meets the principle of «lifelong education», corresponding to the rapid changes in technology and the nature of digital transformations of the society. The article pays special attention to new educational technologies such as: 1) analytical technologies, which are based on the analysis of big data from educational institutions in real time; 2) adaptive (or intellectual) learning, which is based on the principles of personalization of learning and building an individual educational trajectory; 3) Smart education, using learning tools in an interactive educational environment with elements of distance and mobile education. The methodological basis of the research is a systematic approach and general methods of scientific knowledge, such as analysis, synthesis, generalization.   The relevance of the topic is associated with increased attention to the problem of matching the quality of the Russian education with the promising tasks of the digital transformation of the Russian society.   Key conclusion. A high professional level of the personnel reserve, which will be able to practically implement state digitalization programs, is possible and is associated with the construction of a new concept of modern education.